Experimental investigationof water uptakes on modified AQSOA type zeolites under static and dynamic conditions - Shwun, Lai Win (2018)
Global warming has become a serious threat due to the use of CFC and HCFC assisted refrigerants and large emission of CO2 into the atmosphere. Therefore, it is important to utilize renewable energy driven adsorption cooling system that reduces the electricity consumption and mitigates the global warning effects. Hence, researches on adsorbent materials are carried on to improve the performances of absorption chiller system which may replace the conventional vapour compression system with the reduction of electricity consumption. However, the adsorption chiller needs large space due to large quantity of adsorbents required. Therefore, the improvement of water adsorption performance is essential to reduce the size of the chiller. In this report, different % weights of CaCl2 are impregnated into AQSOA-Z05 zeolite to enhance the water adsorption capacity. At first, nitrogen adsorption is conducted to measure the porous characteristics such as BET surface area, pore volume and pore size distributions. Later, the modified adsorbents undergo the gravimetric water adsorption experiment at the temperature of 25°C, 35°C, 45°C and 60°C with the relative pressures varying from Henry’s region up to the saturated pressure under static and dynamic conditions. Finally, Charkraborty-Sun adsorption isotherm model is fitted with experimentally measured water isotherms data to understand the interaction between the modified adsorbent and the water. The kinetics model based on Langmuir analogy is used to capture the kinetics parameters of modified zeolite-water system. Hence, the kinetics rates are found higher than the parent AQSOA-Z05 zeolite and the uptake-offtake difference per adsorption-cooling update is also found higher. Thus, impregnation CaCl2 in AQSOA is a potential solution for the improvement of adsorption chiller performances.